Modelling the pH dependence of the kinetics of aerobic p-nitrophenol biodegradation - Carrera, Julián; Martín-Hernández, Mariángel; Suárez-Ojeda, María Eugenia; Pérez, Julio (Journal of hazardous materials, 2011)
There are a number of publications in the literature that might indicate a connection between pH and the kinetics of the aerobic p-nitrophenol (PNP) biodegradation. In this study two hypotheses were postulated to elucidate the kinetics dependence on pH: (i) the substrate inhibition does not depend on the pH value, therefore the half-saturation coefficient and the substrate inhibition constant will be the same at any pH and (ii) the substrate inhibition depends on the pH value, therefore the half-saturation coefficient and the substrate inhibition constant will have a different value depending on the pH. A PNP-degrading activated sludge was used to carry out three batch respirometric experiments at different pH values: 6.5±0.1, 7.0±0.1, 8.0±0.1. The ability to describe the experimental results with the kinetic models derived from both postulated hypotheses was quantitatively evaluated through the norm of the prediction error array. The time course of specific oxygen uptake rate and PNP concentration was satisfactorily described by a Haldane kinetics that includes the pH effect, based on the PNP acid–base equilibrium, on the kinetic parameters. The results suggest that the nonionised form of PNP is the real substrate and also the inhibitor of the aerobic PNP biodegradation.